L´hybridité de la langue française dans Un Sorcier blanc à Zangali de René Philombe - Richard Tsogang Fossi (Multilinguales)
This paper investigates the use of the French language as a tool of literary creativity in the post-independence era in Cameroon. The so-called “standard” and “pure” language, introduced in the colonial period as a means of colonial supremacy, is re-appropriated and subverted in some of its main rules by some writers of the former colonies, according to their rejected culture, which they intend to revive. The analysis of Un Sorcier blanc à Zangali of René Philombe (1969) shows how the author subdues the French language to the expression of his hybrid identity in the postcolonial context, through the use of elements from oral culture on the one hand, and the very linguistic de-centration of the French language on the other hand.